2010
DOI: 10.1186/1476-072x-9-20
|View full text |Cite
|
Sign up to set email alerts
|

Associations between street connectivity and active transportation

Abstract: BackgroundPast studies of associations between measures of the built environment, particularly street connectivity, and active transportation (AT) or leisure walking/bicycling have largely failed to account for spatial autocorrelation of connectivity variables and have seldom examined both the propensity for AT and its duration in a coherent fashion. Such efforts could improve our understanding of the spatial and behavioral aspects of AT. We analyzed spatially identified data from Los Angeles and San Diego Cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
114
1
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(131 citation statements)
references
References 48 publications
11
114
1
5
Order By: Relevance
“…Some studies showed that street connectivity is statistically significantly correlated with active transportation (Berrigan et al, 2010). More specifically, an explicitly geographic approach can strengthen the built environment and physical activity and active transportation.…”
Section: Socio-economical and Environmental Factors Affecting Active mentioning
confidence: 99%
“…Some studies showed that street connectivity is statistically significantly correlated with active transportation (Berrigan et al, 2010). More specifically, an explicitly geographic approach can strengthen the built environment and physical activity and active transportation.…”
Section: Socio-economical and Environmental Factors Affecting Active mentioning
confidence: 99%
“…The geometric, functional and operational characteristics of street intersections usually receive little mention, except for the rough typological features such as the number of streets converging at each node. This, for instance, is the case of the so called spatial connectivity indicators included in the most widely used methods for urban walkability evaluation [16,17], expressed as the number and type of nodes (commonly number of legs joining in each node) within large spatial units (square km, block, neighbourhood). As a result, the incorporation of spatial connectivity indicators into the composite indicators of walkability can lead to unreliable aggregate results, given that they combine detailed data on street segments, with rougher and less detailed description of intersections.…”
Section: Intersections In Walkability Studies: State Of the Artmentioning
confidence: 99%
“…The bicycle mode choice/share is influenced by the presence of bicycle lanes/ paths; the lane width, the volume and speed of motorized traffic; competition for space between drivers and cyclists; the number of stops, traffic lights or other obstacles; the number of intersections and their characteristics, accident risk; and qualitative aspects about bicycle lanes such as continuity and connectivity or the presence of on-street parking (Berrigan, Pickle and Dill, 2010;Broach, Dill and Gliebe, 2012). Menghini et al (2010) conclude that trip length is the dominant factor for route choice, which is consistent with high time costs and/ or costs of physical exertion.…”
Section: B) Route and Destination Characteristicsmentioning
confidence: 99%